Susceptibilidade in vitro a antimicrobianos da Mannheimia haemolytica e da Pasteurella multocida isoladas de ovinos sadios e com doenças respiratórias - Viana, Leomar [UNESP]; Goncalves, Roberto Calderon [UNESP]; Oliveira Filho, José Paes de [UNESP]; Paes, Antonio Carlos [UNESP]; Chiacchio, Simone Biagio [UNESP]; Ribeiro, Márcio Garcia [UNESP] (My University, 2007)
Pasteurella multocida and Mannheimia haemolytica (P. haemolytica) are associated with ovine respiratory diseases. With the purpose of observe the susceptibility in vitro of these organisms against antimicrobials, were collected samples of nasopharingeal (n=180) and oropharingeal (n=82) from ovines healthy and with respiratory disease. Among the antimicrobials tested, the sensibility was greater for enrofloxacin (100%) and florfenicol (100%), for both bacteria. The greater resistance indices for M. haemolytica and P. multocida were observed with tetracyclin (15.64% and 17.65% respectively) and penicillin (1.82% and 4.2%).
In vitro susceptibility to antimicrobials of Mannheimia haemolytica and Pasteurella multocida isolated from healthy ovine and with respiratory diseases
Keywords: Antimicrobials; Mannheimia haemolytica; Ovine; Pasteurella multocida; Respiratory diseases; Bacteria (microorganisms); Ovis